2017
DOI: 10.1093/aje/kwx231
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis Seroprevalence and Ultrasound-Diagnosed Uterine Fibroids in a Large Population of Young African-American Women

Abstract: Reproductive tract infections have long been hypothesized to increase the risk of uterine fibroids. Few studies have been conducted, even for the common infection genital Chlamydia trachomatis (gCT), and only with self-reported gCT data. Our investigation used micro-immunofluorescence serology for gCT to characterize past exposure. We used cross-sectional enrollment data from a prospective fibroid study carried out in the Detroit, Michigan, area; ultrasound examinations systematically screened for fibroids. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Previous studies have yielded contradictory findings for the associations between reproductive tract infections and cancer development. Reproductive tract infections such as bacterial vaginosis and Chlamydia trachomatis infection were reported to be associated with a decreasing risk of uterine fibroids [ 9 , 10 ]; the risk of bladder cancer was reduced among female patients with urinary tract infections but increased among male patients [ 40 ], which were consistent with our results. In contrast, Liu et al found that HPV infection was associated with an increased risk of breast cancer [ 41 ]; Lin et al and Stewart et al found that pelvic inflammatory diseases related to an increasing risk of urinary tract cancer [ 16 ] and ovarian cancer [ 42 ], respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies have yielded contradictory findings for the associations between reproductive tract infections and cancer development. Reproductive tract infections such as bacterial vaginosis and Chlamydia trachomatis infection were reported to be associated with a decreasing risk of uterine fibroids [ 9 , 10 ]; the risk of bladder cancer was reduced among female patients with urinary tract infections but increased among male patients [ 40 ], which were consistent with our results. In contrast, Liu et al found that HPV infection was associated with an increased risk of breast cancer [ 41 ]; Lin et al and Stewart et al found that pelvic inflammatory diseases related to an increasing risk of urinary tract cancer [ 16 ] and ovarian cancer [ 42 ], respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Infections were found to be associated with cancer risks and were further confirmed to influence cancer prognosis [ 2 7 ]. As for female reproductive tract infections, the common gynecological diseases [ 8 ], were found to be associated with risk of uterine fibroids inversely [ 9 , 10 ]. Further studies had shown that the infection influenced a series of inflammatory processes involving in breast cancer development [ 11 ], such as increasing leukocyte infiltration, over-expression of cytokines and chemokines, and activating nuclear factor-κB [ 12 14 ], which suggested that reproductive tract infections might affect the development of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…did not find strong associations ( Moore et al , 2015). In a recent contribution by the same group women seropositive for genital Chlamydia trachomatis were even found to be less likely to have fibroids ( Moore et al , 2018). In line with these findings, in the study by Heinonen et al .…”
Section: Hypothesis and Opinionmentioning
confidence: 99%
“…The ultrasonic probe enters through the puncture hole and directly contacts the surface of the uterus for scanning and obtains the image of the lesion, so that the operator can obtain information such as the location of the lesion and the relationship between the lesion and its adjacent [ 13 ]. Currently, Qinggan Huoxue Recipe and laparoscopic ultrasound are more commonly used in clinical treatment of liver diseases, and the clinical efficacy is good [ 14 , 15 ]. In terms of gynecology, studies have found that transvaginal ultrasound in laparoscopic surgery can find small fibroids that cannot be detected by the naked eye and remove them, which can minimize fibroid residue and reduce the recurrence rate [ 16 ].…”
Section: Discussionmentioning
confidence: 99%